Raw Material Warehouse Layout Model to Improve Storage Effectiveness at PT. Papertech Indonesia Unit II Magelang - Aman, Moehamad; Satya Putra, Handika; Imron Rosyidi, Muhammad (JSE Journal of Science and Engineering, 2025)
PT. Papertech Indonesia Unit II is a recycled paper factory that orders raw materials Old Corrugated Container (OCC) and Mix Waste (MW) is carried out every day, as a result the raw material storage warehouse often experiences excess capacity, so that its arrangement is often irregular. In order to optimize the utilization of the storage warehouse at PT. Papertech Indonesia Unit II Magelang, it is necessary to carry out a design model for the layout of the facility. One of the objectives of designing the layout of the facility is more effective use of space. The design in this study uses the method Dedicated Storage. The results of arranging paper raw materials in the warehouse using the method Dedicated Storage through addition material handling obtained a time effectiveness of 27%. Cost material handling The proposal obtained a 9% reduction in cost efficiency. Travel distance material handling on the proposed layout by 34%, with the warehouse storage capacity increasing by 10%. The proposed raw material storage warehouse layout is based on the method Dedicated Storage consists of 8 blocks, in one block consists of 6 areas, each area consists of 50 slots. The total number of slots that can be accommodated is 2,400 slots, resulting in a 25% increase in slot capacity. The floor area requirement for storing raw materials is 87.78 m x 62.24 m or 5,463 m2thus increasing the utilization of the warehouse area by 7%. The remaining unused warehouse area is 1,662 m2 with a percentage of remaining area of ​​23.32% and utilization of the remaining unused area of ​​20%.